Delayed Effects of Transcutaneous Organophosphate Poisoning in Four Children. Issue 4 (26th November 2015) - Pavlovic, Milen; Neubauer, David; Al-Tawari, Asma A.
Contamination or transcutaneous absorption of organophosphates (OP) is rare and there exist only few reports of such manner of poisoning. We report four children from the same family in whom temporal proximity of the disease onset, a detailed interrogation of parents and exclusion of other clinical differentials, led to the diagnosis of transcutaneous intoxication with organophosphates (diazinon). The contamination occurred during the game with a freshly used poison can. Uncommon clinical picture was marked by delayed signs predominantly reflecting certain nicotinic effects (muscle weakness, cramps) along with subtle neuropathic features occurring throughout a few weeks after initial event. Our illustrative cases can further contribute to the better awareness and understanding of variable spectrum of transcutaneous route of OP poisoning.